(untitled) (The International Journal for Scientific Research, 2025)
Staphylococcus aureus (S. aureus) stands as a prominent pathogen in both hospital and community settings, causing a spectrum of infectious diseases. These range from mild skin and soft tissue infections to more severe conditions like infective endocarditis, osteomyelitis, bacteraemia, and potentially fatal pneumonia. The escalating drug resistance of S. aureus, driven by bacterial evolution and antibiotic misuse, has become a pressing concern in healthcare. Nigella sativa (N. sativa), a member of the Ranunculaceae family, is an herb indigenous to regions spanning the Middle East, Europe, and Western and Middle Asia. This plant has a long-standing history of use as a nutritional supplement and therapeutic agent for various infections and chronic conditions. Given S. aureus’s remarkable adaptability to antibiotic pressure, which poses a significant health challenge, the exploration of novel antimicrobial agents has become imperative. A research initiative at the University of Tobruk sought to investigate the antibacterial efficacy of N. sativa seeds against S. aureus. The study employed the cup-plate agar diffusion technique under controlled laboratory conditions. Results indicated that while aqueous extracts of N. sativa seeds failed to inhibit S. aureus growth, the alcoholic extract demonstrated clear inhibitory effects, even at the lowest tested concentration. These findings corroborate the antibacterial properties of N. sativa seeds and provide scientific backing for the plant’s traditional application in treating bacterial